The Expression of Glycoprotein Genes in the Inflammatory Process of Kawasaki Disease - Kuo, Kuang-Che; Yang, Ya-Ling; Lo, Mao-Hung; Cai, Xin-Yuan; Kuo, Ho-Chang; Huang, Ying-Hsien (Frontiers in Pediatrics, 2020)
Background Kawasaki disease (KD) is the most common form of febrile coronary vasculitis disease to occur in children. Early diagnosis and proper therapy can prevent the complication of coronary artery lesions (CAL). The main pathogenesis of KD is an inflammatory process related to the host’s genetic characteristics. In innate human immunity, the interaction between leukocytes and glycoprotein plays an important role against microbes. The purpose of our study was to understand the role of leukocytes’ glycoprotein genes during the acute phase of KD. Materials and Methods We enrolled a total of 97 subjects from a medical center. Of those, 24 subjects were healthy controls, and 24 subjects were fever controls; the other 49 subjects were KD patients who had had blood samples taken both before and after IVIG treatment. We collected the total RNA from leukocytes and performed a quantitative polymerase chain reaction for the HP, GRP84, and CLEC4D genes in real time. Results Compared with both the healthy and fever controls, the upregulation of HP, GRP84, and CLEC4D genes was significant in peripheral leukocytes during acute-phase KD. The transcriptional level of these respective genes not only demonstrated a positive correlation with each other, but were also effective predictors for KD (all auROC >0.87) according to the ROC curve analysis. The hyper-expression of these three genes was significantly associated with IVIG resistance, but not CAL formation. Conclusions Our study demonstrates that the expression of HP, GRP84, and CLEC4D genes of leukocytes play an important role in the pathogenesis and primary IVIG response during the acute inflammatory process of KD.